2023
DOI: 10.3389/fenvs.2023.1174875
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution and influencing factors of coupling coordination between urban resilience and high-quality development in Yangtze River Delta Area, China

Abstract: The coordination relationship between urban resilience and high-quality development is of paramount importance for improving disaster-alleviated resilient governance and sustainable development in response to the globalized crisis. However, few studies have investigated the coupling between urban resilience and high-quality development. Therefore, based on the analysis of the coupling and coordination mechanism between urban resilience and high-quality development, this paper innovatively calculates the indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…Some preliminary studies have shown that the imbalance of high-quality development in service industry is prominent [3,14], with agglomeration effects [31][32][33]. The Yangtze River Delta region shows an inverted 'U' shape of high-quality development, with significant regional differences [34,35]. These literatures make certain contribution to the field, with methods focusing on entropy weighting [36,37], Durbin model [34,38], Moran's index [5,39].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some preliminary studies have shown that the imbalance of high-quality development in service industry is prominent [3,14], with agglomeration effects [31][32][33]. The Yangtze River Delta region shows an inverted 'U' shape of high-quality development, with significant regional differences [34,35]. These literatures make certain contribution to the field, with methods focusing on entropy weighting [36,37], Durbin model [34,38], Moran's index [5,39].…”
Section: Introductionmentioning
confidence: 99%
“…The Yangtze River Delta region shows an inverted 'U' shape of high-quality development, with significant regional differences [34,35]. These literatures make certain contribution to the field, with methods focusing on entropy weighting [36,37], Durbin model [34,38], Moran's index [5,39]. Although these methods can reflect the level of highquality development more accurately, they focus more on correlation analysis [40], and it is difficult to reflect the agglomeration effect and transfer regulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robustness Tests. In order to test the validity of the estimation results, two types of robustness tests were conducted: replacement of the spatial weight matrix and sub-sample regression [ 55 ]. Firstly, the economic weight matrix and the economic geographic weight matrix were used as replacements for the spatial weight matrix, and the Separate regressions were performed to compare whether there were significant changes in the results.…”
Section: Results Analysismentioning
confidence: 99%
“…The kernel density estimation curve can portray the distribution pattern, location, and extension of the random variables, so it can be used to examine the time-series evolutionary variation characteristics of the coupling coordination degree of LUFs. In addition, the trend surface can be used to fit a mathematical surface to illustrate the spatial trends and distribution patterns of the observed values of geographic elements over a large spatial span, which will then be used to further analyze the overall spatial divergence trends of the coupling coordination within the study area [32].…”
Section: Introductionmentioning
confidence: 99%